Nationwide Earthquake Risk Model for Wood-Frame Houses in Canada - Goda, Katsuichiro (Frontiers in Built Environment, 2019)
Quantitative seismic risk assessments involve hazard characterization, exposure database, vulnerability assessment, and uncertainty modelling, and promote consistent risk management actions, when conducted systematically across a country. This study implements a performance-based earthquake engineering methodology to develop a nationwide earthquake risk model for Canadian wood-frame houses by integrating probabilistic seismic hazard analysis results provided by the Geological Survey of Canada and seismic fragility functions derived from incremental dynamic analysis. To facilitate the implementation of the seismic risk analysis method, an in-house probabilistic seismic hazard analysis tool for Canada is developed and used to verify the accuracy of the adopted approach of approximating the upper tail of the seismic intensity measure distribution and to generate detailed seismic disaggregation results for ground motion record selection and seismic fragility modelling purposes. By integrating the preceding two elements via Monte Carlo methods, a full seismic risk curve can be obtained in a computationally efficient manner. The approach is applied to 1,620 representative locations used for the 2016 Canadian Census and thus facilitates the development of seismic risk maps of key risk metrics that are derived from exceedance probability curves in terms of earthquake damage/loss ratio. The developed seismic risk maps serve as valuable decision-support tools to implement risk-based management strategies consistently across Canada.